1987
DOI: 10.1002/j.1460-2075.1987.tb04831.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Agrobacterium tumefaciens vir gene expression generates multiple single-stranded T-strand molecules from the pTiA6 T-region: requirement for 5′ virD gene products.

Abstract: Agrobacterium tumefaciens transfers its Ti‐plasmid T‐DNA to plant cells. This process is initiated by plant‐induced activation of the Ti‐plasmid virulence loci, resulting in the generation of single stranded (ss) cleavages of the Ti‐plasmid T‐DNA border sequences (border nicks) and ss linear unipolar T‐DNA molecules (T‐strands). A single T‐strand is produced from the two‐border T‐region of the pGV3850 nopaline plasmid. In this paper the induced molecular events for the complex T‐region of the pTiA6 octopine pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
123
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(129 citation statements)
references
References 19 publications
5
123
0
1
Order By: Relevance
“…In vivo in Agrobacterium, VirD1/D2 are both required for the nicking reaction (Scheiffele et al, 1995;Stachel et al, 1987;Yanofsky et al, 1986). In vitro, VirD2 alone nicks ss oligonucleotides bearing the T-DNA border sequence (Jasper et al, 1994;Pansegrau et al, 1993a).…”
Section: Nic Sites and Nicking Enzymes (Table 1 Item 8)mentioning
confidence: 99%
“…In vivo in Agrobacterium, VirD1/D2 are both required for the nicking reaction (Scheiffele et al, 1995;Stachel et al, 1987;Yanofsky et al, 1986). In vitro, VirD2 alone nicks ss oligonucleotides bearing the T-DNA border sequence (Jasper et al, 1994;Pansegrau et al, 1993a).…”
Section: Nic Sites and Nicking Enzymes (Table 1 Item 8)mentioning
confidence: 99%
“…Studies of the interaction of T-DNA borders with VirDl and VirD2 proteins in either Agrobacterium or Escherichia coli revealed that VirDl is required for efficient binding of VirD2 to the border repeats. The VirDlVirD2 complex is known as a sequence-specific endonuclease-topoisomerase that introduces a nick in the conjugative T-strand (the "bottom strand") at the third base of the 25-bp border (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…A regulatory system consisting of VirA (a transmembrane sensor) and VirG (a transcriptional activator) regulate vir gene expression (24,25,44). Following vir induction, the VirDl and VirD2 proteins provide topoisomerase (19) and endonuclease (42,56) functions that initiate T-DNA processing by introducing a site-and strand-specific nick within conserved 25-bp cis-acting sequences, termed borders, that delineate the ends of the T-DNA molecule (2,31,47). A strand displacement synthesis reaction probably initiates at the 5' border cleavage site to generate a linear, single-stranded molecule (the T strand) corresponding to the bottom strand of the T-DNA between the borders (2,41,42).…”
mentioning
confidence: 99%